Adhesion of a chondrocytic cell line (USAC) - Emi Imoto (J Oral Pathol Med)
Chondrocytes produce various extracellular matrices during chondrogenesis. Fibronectin and proteoglycan are major extracellular matrix proteins in cartilage tissue, but the interactions between them are not clear.